Co-Creating Knowledge and Innovation through Online Communities: The Case of a Mobile Virtual Network Operator - Hawkins, Matthew (2012)
This study investigates the co-creation of knowledge and innovation with customers, exploring the types of contributions made to the innovation process by customers and the value created for the company and its customers by the co-creation process. Additionally, this study explores the dynamics of the process of knowledge sharing between customers.